Attempt to correlate surface physics and chemical properties : molecular beam and Kelvin probe investigations of Ce 1-x Zr x O 2 thin films - Kolekar, Sadhu K.; Dubey, Anjani; Date, Kalyani S.; Datar, Suwarna; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2016)
What is the correlation between physical properties of the surfaces (such as surface potential, electronic nature of the surface), and chemical and catalysis properties (such as chemisorption, sticking probability of surface)? An attempt has been made to explore any correlation that might exist between the physical and chemical properties of thin film surfaces. Kelvin probe microscopy (KPM) and the molecular beam (MB) methods were employed to carry out the surface potential, and oxygen adsorption and oxygen storage capacity (OSC) measurements on Ce1−xZrxO2 thin films. A sol–gel synthesis procedure and spin-coating deposition method have been applied to make continuous nanocrystalline Ce1−xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (35–50 nm); however, surface roughness and porosity inherently changes with CZ composition. MB studies of O2 adsorption on CZ reveal high OSC for Ce0.9Zr0.1O2, which also exhibits highly porous and significantly rough surface characteristics. The surface potential observed from KPM studies varied between 30 and 80 mV, with Ce-rich compositions exhibiting the highest surface potential. Surface potential shows large changes after reduction or oxidation of the CZ film demonstrating the influence of Ce3+/Ce4+ on surface potential, which is also a key to catalytic activity for ceria-based catalysts. The surface potential measured from KPM and the OSC measured from MB vary linearly and they depend on the Ce3+/Ce4+ ratio. More and detailed studies are suggested to arrive at a correlation between the physical and chemical properties of the surfaces.

C-H activation of methane to formaldehyde on Ce1-xZrxO2 thin films: a step to bridge the material gap - Dubey, Anjani; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (ChemCatChem, 2016)
Ce1−xZrxO2 (CZ) thin films were prepared by a combination of sol–gel and spin-coating methods and were evaluated for the C−H activation of methane by using a molecular beam set-up with the aim to bridge the material gap. The C−H activation of methane begins at 950 K, and a Ce-rich CZ composition displays a high selectivity (4–12 %) to the partially oxidised product, formaldehyde. A 10–12 % selectivity towards HCHO with 1.6 % methane conversion was observed with methane-rich CH4/O2 reactant compositions at 1050 K. Short contact times, prevalent under molecular beam conditions, could be a possible reason for HCHO formation. Although combustion products were observed instantly upon shining the mixture of reactants on CZ surfaces, up to 20 s delay was observed before formaldehyde generation, which indicates that the oxygen vacancy migration contributes to the rate-determining step and the diffusion-controlled nature of the reaction. A burst in HCHO generation at the point of molecular beam opening, after beam-closed conditions, suggests that the diffusion of oxygen vacancies to the surface is the reason for HCHO formation. Kinetics results also indicate the necessity of reduction sites for HCHO generation.

C-H activation of methane to syngas on MnxCe1-x-yZryO2 - a molecular beam study - Dubey, Anjani; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Chemcatchem, 2016)
Mn-doped ceria zirconia thin films (MnxCe1-x-yZryO2, MCZ) were employed as flat model catalyst surfaces for CH4 activation. MCZ films exhibit characteristics of single crystal and powder materials, such as smooth surfaces and porosity. From molecular-beam studies, it has been identified that the oxygen storage capacity increases with Mn content. Mutually exclusive observation of H2O or a mixture of products (CO2+ CO + H-2) occurs, when the reactants was allowed to react directly on MCZ, underscoring their formation or prevention (and consumption), respectively. The results suggest that there is competition and cooperation among different elementary reactions under complementary conditions. From a significant partial oxidation of CH4 through C-H activation, it is found that formation of syngas begins at 700 K and the reaction rate increases with increasing temperature. Kinetic evidences indicate that the reaction proceeds through a combustion-reformation pathway.

Porous thin films towards bridging the material gap in heterogeneous catalysis - Dubey, Anjani; Kolekar, Sadhu K.; Gnanakumar, Edwin S.; Roy, Kanak; Vinod, C. P.; Gopinath, Chinnakonda S. (Catalysis, Structure & Reactivity, 2016)
An attempt has been made to bridge the material gap, existing between ideal single crystals and real-world powder nanocatalyst employed in surface science and heterogeneous catalysis, respectively. Simple wet chemical method (sol–gel and spin-coating deposition) has been applied to make continuous Ce1 − xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (~40 nm) and smooth surface characteristics. Uniform thickness and surface smoothness of the films over a large area was supported by a variety of measurements. Molecular beam (MB) studies of O2 adsorption on CZ surfaces reveals the oxygen storage capacity (OSC), and sticking coefficient increases from 400 to 800 K. Porous nature of Ce-rich CZ compositions enhances O2 adsorption and OSC, predominantly due to O-diffusion and redox nature, even at 400 K. A good correlation exists between MB measurements made on CZ films for oxygen adsorption, and OSC, and ambient pressure CO oxidation on powder form of CZ; this demonstrates the large potential to bridge the material gap. CZ was particularly chosen as a model system for the present studies, since it has been well-studied and a correlation between surface science properties made on thin films and catalysis on powder CZ materials could be a litmus test. Ambient catalysis on ceria-zirconia nanocatalyst correlates well with surface properties measured through molecular beam on thinfilm and close the material gap.

Electronic structure evolution from metallic vanadium to metallic VxOy: a nappes study for o2+v gas-solid interaction - Ranjan, Ravi; Mhamane, Nitin B.; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2022)
Gas-solid interactions between molecular oxygen and metallic vanadium surfaces and the systematic evolution in the electronic structure of vanadium oxide (VOx) surfaces have been explored in the present work by near-ambient pressure photo-electron spectroscopy (NAPPES). The current article studies the evolution of various oxides of vanadium as a function of partial pressure of O2 (ultrahigh vacuum to 1 mbar), temperature (298- 875 K), and the exposure time to oxygen (up to 18 h). Valence -band (VB) and core-level spectral measurements recorded with UV (He-I = 21.2 eV) and Al K alpha (1486.6 eV) photons, respectively, show interesting changes. (1) Oxidation is limited to the top layers of vanadium at 298 K and up to a partial pressure of 1 mbar O2. About 50% of vanadium gets oxidized, and the remaining amount exists as metal within the top 10 nm. (2) Metallic vanadium disappears above 625 K, and it is predominantly oxidized to a mixture of V4+ and V5+ oxidation states at a 0.1 mbar partial pressure of O2. Points 1 and 2 suggest the predominantly thermodynamically controlled nature of vanadium oxidation through oxygen diffusion into the subsurface and bulk layers. (3) The Fermi-level (EF) feature observed first at >= 725 K at a 0.1 mbar O2 pressure demonstrates the formation of metallic VO2; however, its metallic nature is preserved even at ambient temperature due to interweaving nanodomains of VOx with VO2. (4) Only partial conversion of surface layers to V5+ (V2O5) along with VO2 and V2O3 (within the probing depth of 8-10 nm by near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS)) was observed even after prolonged heating (18 h) in 1 mbar O2 pressure. (5) The nature of the surface changes between metal and semiconducting/ insulator oxides is substantiated by the observation of changes in work function (phi) and EF features. Typical VB features and Fermi intensity of V-metal and vanadium oxides were observed, and the results were corroborated with core-level and VB spectra. The present results extend the capabilities of NAPPES to explore the electronic structure evolution as a function of reaction conditions and underscore its relevance to areas such as heterogeneous catalysis and sensing.

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG